Review on researches and main influencing factors on mechanical properties of offshore wind power cables - Xu Qin; Mengmeng Zhang; Shixiao Fu; Huailiang Li; Jing Hou; Yuwang Xu (Journal of Ocean Engineering and Science, 2025)
With the rapid development of offshore wind farms, the usage and quantity of offshore wind power cables have increased significantly. However, the existing research on offshore wind power cables still cannot meet the stringent requirements of deep-sea environments. Therefore, improving the understanding of the mechanical performance of offshore wind power cables and their influencing factors holds profound implications. This paper provides an overview of existing numerical and experimental researches on mechanical performance of offshore wind power cables. The relationship between various mechanical properties of offshore wind power cables and their complex cross-sectional structural forms are systematically elaborated. The limitations of these researches are analyzed. And a prospective outlook on future research directions is provided, aiming to guide reliable engineering applications of offshore wind power cables in complex marine environments.